Accuracy of 3-D planning and navigation in bone tumor resection - Ritacco, Lucas (2013)
Surgical precision in oncologic surgery is essential to achieve adequate margins in bone tumor resections. Three-dimensional preoperative planning and bone tumor resection by navigation have been introduced to orthopedic oncology in recent years. However, the accuracy of preoperative planning and navigation is unclear. The purpose of this study was to evaluate the accuracy of preoperative planning and the navigation system.A total of 28 patients were evaluated between May 2010 and February 2011. Tumor locations were the femur (n=17), pelvis (n=6), sacrum (n=2), tibia (n=2), and humerus (n=1). All resections were planned in a virtual scenario using computed tomography and magnetic resonance imaging fusion. A total of 61 planes or osteotomies were performed to resect the tumors. Postoperatively, computed tomography scans were obtained for all surgical specimens, and the specimens were 3-dimensionally reconstructed from the scans. Differences were determined by finding the distances between the osteotomies virtually programmed and those performed. The global mean of the quantitative comparisons between the osteotomies programmed and those obtained through the resected specimen was 2.52±2.32 mm for all patients.Differences between osteotomies virtually programmed and those achieved by navigation intraoperatively were minimal.